Seismic fragility analysis of RC bridges in high seismic regions under horizontal and simultaneous horizontal and vertical excitations. (March 2022) - Thapa, Sunil; Shrestha, Yadin; Gautam, Dipendra
Abstract: Although Himalayan highways generally pass close to the active seismic faults, near field excitation effects are not considered in designing bridges. The effect of strong vertical shaking is known to cause several anomalous and remarkable consequences in bridges. To this end, we present a comparative seismic vulnerability analysis of representative RC bridge from Nepal Himalaya, considering horizontal only and simultaneous horizontal and vertical excitations. Fragility functions for longitudinal and transverse directions considering horizontal only and simultaneous horizontal and vertical excitations are constructed for representative RC bridge from Asian Highway-2 (AH-2) in Nepal that generally follows the same alignment as that of one of the very active seismic faults in the region. Analytical fragility functions are also compared with the existing empirical fragility functions. The results depict that the horizontal response parameters, such as displacement and displacement ductility, are not considerably affected by the vertical ground motion, but the effect is found to be increasingly significant for higher damage states. The sum of observations highlights that the transverse direction of the bridge will be more prominent while considering vertical excitation effects together with the horizontal excitation rather than the horizontal excitation only.